Physical health of preclinical medical students during Covid-19 - Nor Azlan, Nur Khairunnisa; Razman, Amalia Izzati; Shaik Mohd Nizam, Nur Alia Iman; Anuar, Muhammad Ashraf Fithri; Abdullah, Muhammad Haikal; Ahmad Ashhar, Muhammad Ikmal Arif; Mohamad, Mohammad Muaz; Shahrir, Shahida Athirah; Johari, Muhammad Luqman ‘Afif; Zulkifli, Ahmad Najmi Abid; Zamani, Muhammad Razin; Azani, Muhammad Adam; et al. (2021)
Due to the COVID-19 pandemic, several preventive measures have been put in place including movement restriction and closure of non-essential services in Malaysia including educational premises and shifting towards online learning. Physical inactivity may impact medical students’ quality of life, particularly their physical and mental health, as both are especially influenced by doing physical activity. This study aimed to assess the physical health of medical students during the pandemic.